An epidemiologic study of the Thai Stroke Rehabilitation Registry (TSRR): A multi-center study - Vilai Kuptniratsaikul (2018)
Objective: To perform the registry of stroke patients receiving the in-patient comprehensive rehabilitation program at main tertiary hospitals from March to December 2006. Material and Method: Demographic data including medical history and pathology of stroke were recorded. All subjects received a comprehensive rehabilitation program until they reached their rehabilitation goals or discharge criteria. Results: Three hundred twenty seven patients met the inclusion criteria. The mean age was 62 +/- 12 years, and 59% were males. Most of the patients were married (73.1%), lived in an urban area (62.1%), and had an education level of primary school or lower (58.7%). The median duration from onset to admission for rehabilitation was 24 days. The major medical history was hypertension (74.9%), followed by dyslipidemia (54.4%), diabetes mellitus (26.6%), and ischemic heart disease (18.0%). Fifty-one (15.6%) patients had a history of previous stroke. Cerebral infarction was found in 71.9%, including thrombosis (45.3%), lacuna infarction (15.3%), and emboli (8.0%) and 28.1% had hemorrhagic stroke. On admission, more than half (51.8%) had cognitive impairment and one-third (31.5%) had bowel-bladder problems. Almost all of the patients (99.4%) had family support. Either their spouse or siblings had undertaken the main caregiver role (46.5% and 40.4% respectively). However, more than 80% of the patients were discharged to their own homes or immediate family's house. Conclusion: This was the first multi-center registry of inpatient stroke rehabilitation in Thailand. It presented the epidemiologic aspects in order to become national data of stroke patients receiving medical rehabilitation services.